Causes and consequences of long-run currency appreciation: The Swiss case - Peter Kugler (Aussenwirtschaft, 2017)
The econometric analysis of a panel of currencies after the transition to flexible exchange rates indicates that the real exchange rate of the Swiss franc against six major currencies is trend stationary and that the elasticity of the nominal exchange rate with respect to the relative price level is close to 1. Moreover, the dollar and pound real exchange rates appear unrelated to the GDP share of the Swiss financial sector over the years 1916-2010. This confirms previous findings for the pound and dollar for a currency panel during the flexible exchange rate period, namely, that the real appreciation of the Swiss franc in the flexible exchange rate period appears to be a "real" phenomenon not related to monetary and financial developments, and it mainly creates a risk for the stock of Swiss net foreign assets.
Keywords: 330